The Efficacy of Mindfulness Counseling Management in Improving Self-Regulation: An Action Research Study in an Islamic High School - Ahmad Zarkasyi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The main objective of this article is to explain the management of guidance and counseling using mindfulness-based techniques to help students improve self-regulation at Madrasah Aliyah Miftahul Ulum Lumajang. This type of research is guidance and counseling action research. The research subjects were the principal, guidance and counseling teachers, and students. Data collection used in-depth interviews, observation, and documentation—data analysis with the stages of data reduction, data presentation, and conclusion. Based on the study's results, it can be concluded that the management of guidance and counseling at the school helps students organize their study time by preparing daily schedules, determining task priorities, developing effective study techniques, maintaining good relationships with students, and defining and clarifying problems.